METHODS OF TEACHING MATHEMATICS IN PRIMARY GRADES - Rahmatjonzoda is the son of Ahrorjon Ahmat (Journals Park Publishing, 2023)
In the article allows students' work to determine their level of preparation for certain sections of the program, to monitor their growth and development during a certain period of training. For example, special written and graphic work is carried out with the purpose as a result of the examination, children's knowledge and skills in mathematics should be clearly visible; opinions are expressed about the factors that show that students are progressing and to what extent, performing such special tasks in a certain period of time
Keywords: factor, basis, technology, opinion, reflection, teacher, child, writing.